Trends in diabetes mellitus and related costs among hospital admissions in Switzerland, 2012–2020 - Hassan Abu Obaid; Pedro Marques-Vidal (Diabetology & Metabolic Syndrome)
Abstract Background In Switzerland, the prevalence of diabetes mellitus (DM) has increased in the general population, but little is known regarding DM-related hospitalizations and their impact on mortality and health costs. Hence, our objectives were to assess (1) the evolution of hospitalizations for DM as first diagnosis and as comorbidity; (2) the association of DM with ICU admission, length of stay (LOS), in-hospital mortality and costs. Methods Swiss hospital discharge data for period 2012–2020. Type 1 (T1DM), type 2 (T2DM) and other types (OTDM) of DM were considered. Results Between 2012 and 2020, the number of hospitalizations (% total) increased from 4204 (0.27) to 4980 (0.45) for T2DM, 539 (0.05) to 854 (0.08) for T1DM and 221 (0.02) to 381 (0.03) or OTDM. Hospitalizations with DM as comorbidity increased from 89,752 (8.6) to 128,700 (11.7) for T2DM, 2934 (0.29) to 3536 (0.32) or T1DM and 5774 (0.58) to 9143 (0.83) for OTDM. Compared to non-DM hospitalizations, all types of DM had a higher likelihood of lower limb amputation; hospitalizations for T1DM had a higher likelihood of ICU admission: odds ratio and 95% CI: 3.38 (3.19–3.59), while T2DM had higher LOS: 5.5 ± 1.0 vs. 5.1 ± 1.0 days, and all DM types had a lower odds of in-hospital mortality. Patients with any type of DM as comorbidity had a longer LOS than patients without. Total cost of DM rose from CHF 42 million in 2012 to almost 100 million in 2019 and decreased afterwards. Conclusion DM represents an increasing health and economic burden in Switzerland.